Temporality and Atemporality in the Language of Biblical Poetry - Notarius, Tania (Journal of Semitic studies, 2011)
In this paper I claim that, in spite of the tenseless character of the verbal inflection in BH, the temporal interpretation of verbal statements in a poetic text is possible as in any other type of discourse, if we systematically assess the rendering of deictic, anaphoric and sequential times, and take into account the pragmatic principles that control temporal implications of aspectual and modal forms in texts. However, many statements in biblical poetic discourse remain ambiguous as regards their temporal interpretation due to the basic ‘atemporal perspective’ at work. Atemporality in language and discourse correlates with two main phenomena — stativity and illocatability. Stativity in language is associated with such verbal constellations as states and general statives. Stativity in discourse has two sides: there are discourse modes that generally incorporate static entities; some discourse modes demonstrate atemporal text-progression. Illocatability in language is exemplified through the problem of the temporal structure of general statives. Illocatability in discourse is associated with deficiency in the context of deictic and anaphoric elements, necessary for temporal interpretation; in biblical poetry the deficiency of temporal indications can be intensified by poetic terseness and flexibility. Most of the features, associated with atemporal perspective, are not specific to poetic language; they have a universal character and may occur in other discourse types as well. However, the high concentration of all the ‘atemporal’ phenomena and their foregrounded, pragmatically prominent position in a poetic text make biblical poetic speech more ‘atemporal’ than most other speech types. In this paper, I adopt a comprehensive approach to temporality, formulated by Carlota Smith. The investigation is based on the linguistic analysis of poetic fragments from the Torah and Former Prophets (the so-called ‘archaic’ poetry) and the classical prophetic poetry from the books of Amos, Hosea and Isaiah.